Estimasi Manufaktur Exspantion Joint di Bengkel Fabrikasi PT. Semen Padang - Desmarita Leni; Venny Selviaty (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
Estimated Expansion Joint made in the fabrication workshop of PT. Semen Padang is one of the connection equipment used in kilns to support cement production in cement factories. The estimation is carried out by Expansion Joint analysis of the wear of the plate material by calculating the stretch of the plate used. The purpose of this estimate is to find out how much material is used, how long it takes, and how much equipment is used when making expansion joints and to calculate the estimation of the expansion joint welding process. After doing the calculations to determine the specifications of the expansion joint to be installed, From the results of the analysis and calculations, it is known that the processing time is 33.05 hours, the total electrode used is 6.587 kg, and the welding time is 1474,433 minutes, or 24.58 hours.